Childhood Sexual Abuse : Event, Fact or Structure - Levett, Ann (PINS-Psychology in Society, 1987)
In attempting to develop a different approach to understanding various areas of human life psychologists have been commenting contradictory, on the range of discourses, many which dominate social practices (e.g. Gergen, 1985, Herre, 1984, Moscovici, 1984, Sampson, 1986). These processes contribute to the production of each human subject, to the construction of individual identity and emotional life, and construct the meanings imputed to interpersonal exchanges, including relations between men and women and between adults and children. In order to make sense of the complexities of human behaviour, we need to take apart both the commonplace notions and the dominant, accepted explanations of cause-effect relationships. In any particular discourse, because of dominant sociocultural forms of understanding, attention tends to focus on certain specifics with a noticeable lack of attention to attendant phenomena, Where perceptible, the gaps are likely to be a fruitful locus for the study of contradictions. In a social constructionist view, where any discussion about the world is seen as "an artefact of communal interchange" (Gergen, 1985; p.266), psychological inquiry itself may be evaluated. This approach forces us to re-examine dominant systems of thought and to reflect on widespread conceptions of knowledge, which leads to insights concerning the purposes of knowledge, and how it is transformed.